Green paper : towards a national industrial policy (Jamaica Information Service KingstonJM, 1994)
Seeks to address the major constraints facing the productive sectors, in order to improve competitive advantage in international markets. Includes a statement on the definition and scope of industrial policy, its rationale and objectives, and a description of the main components of the industrial policy.
DC